The Authority of Al-Sima' in Ushul An-Nahwi: An Analysis of Al-Suyuthi's Thought in the Book Al-Iqtirah: Otoritas Al-Sima' dalam Ushul An-Nahwi: Analisis Pemikiran Al-Suyuthi dalam Kitab Al-Iqtirah - Ashar, Andi Muhammad; Hamzah, Andi Abdul (Program Studi Pendidikan Bahasa Arab, Fakultas Tarbiyah, IAIN Kediri, 2025)
Nahwu (Arabic grammar) is a fundamental discipline in Islamic studies, particularly for understanding the Qur'an and Hadith. Debates regarding authoritative sources for establishing grammatical rules have long existed, with the concept of al-sima' (direct reception from eloquent native Arab speakers) being a primary foundation. This research aims to analyze the concept of al-sima' according to Imam Jalaluddin al-Suyuthi (d. 911 H/1505 M) in his work